Design and Analysis of a Phase Shifted Full Bridge Converter for High Efficiency Operation - Larsson, Simon; Karlsson, Johannes (My University, 2023)
Abstract Saab investigates if there is a possibility to replace an existing DC/DC converter with an alternative converter design. Saab therefore wanted a phase shifted full bridge designed and constructed, capable of delivering 1.2 kW for an output voltage of 56 V, with a maximum output voltage ripple of 1%. The input voltage range is set to 350-400 V. The final design was then compared with an alternative solution, an LLC converter, in order to compare possible advantages with each solution. The phase shifted full bridge converter was successfully designed and implemented in simulations. A list of components and a circuit schematic to realise the design in a physical implementation was then presented and the converter was constructed. Due to oscillations and a faulty snubber design, the phase shifted full bridge converter could not reach the aspirations and the maximum output power was limited to 400 W. The voltage ripple was not within the goal of 1% and the efficiency of the LLC was higher. However, the advantages of using a phase shifted full bridge compared to a LLC was also presented where a fully operational converter was considered.